Transparansi dan Akuntabilitas dalam Administrasi Keuangan Sekolah/Madrasah - Ana Saritilawa; Dwi Alyanti; Lailatul Qodriah; Zatu Muharroh; Aprizal Ahmad; Rully Hidayatullah (CV. ITTC INDONESIA, 2026)
Educational financial management is a crucial aspect in realizing good governance in educational institutions. This study aims to analyze the application of the principles of transparency and accountability in school/madrasah financial administration and identify their role in improving the quality of educational management. The research method used is a qualitative approach with a library research design, which examines various scientific literature, indexed journals, and related official documents. The results indicate that the integration of transparency and accountability serves as an important instrument for preventing budget irregularities and increasing public trust. However, its implementation still faces obstacles such as limited human resource (HR) competency, a low culture of openness, and suboptimal use of information technology. This study recommends strengthening the competency of financial managers, digitizing reporting systems through applications such as ARKAS, and increasing stakeholder participation in financial oversight to achieve sustainable educational quality.